The Growth-Interest Rate Cycle in the United States and its Consequences for Emerging Markets - Carmen Reinhart; Guillermo A. Calvo; Eduardo Fernández-Arias; Ernesto Talvi (Inter-American Development Bank, Research Department, 2001)
At the time of writing there were widespread concerns about the health of the U. S. economy. There is conclusive evidence that the pace of growth has slowed, which has prompted the Federal Reserve to cut interest rates on two occasions (a total of 100 basis points thus far). As usual, when faced with this kind of turning point, analysts and policy makers alike wonder whether the United States will achieve a soft landing or whether the downturn is more serious and protracted in the worst scenario, the new weakness could signal the end of the new economy. Furthermore, recent inflation surprises have not been encouraging, as higher-than expected inflation numbers may curtail the Federal Reserve`s desire and ability to act counter cyclically.
Keywords: 330; Wirtschaftswachstum; Geldpolitik; Kapitalmobilität; USA